2010
DOI: 10.1007/s11113-010-9195-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Analyses of Gay Male and Lesbian Partnering in the Metropolitan United States in 2000

Abstract: This paper has two objectives. Using data from the 2000 census, we develop for each of the 331 metropolitan statistical areas (MSAs) of the United States in 2000 an index of gay male partnering and an index of lesbian partnering. Drawing on the theoretical perspective of human ecology, we propose and test an assortment of hypotheses relating characteristics of the metropolitan areas with the gay male and lesbian partnering indexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…30 We choose to follow an approach used by Walther et al, 31 that calculates a same-sex couple rate per 1000 coupled households, shown for male couples:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 We choose to follow an approach used by Walther et al, 31 that calculates a same-sex couple rate per 1000 coupled households, shown for male couples:…”
Section: Methodsmentioning
confidence: 99%
“…12 Same-sex couples, like other couples, tend to migrate toward regions with better jobs, more temperate weather, lower crime, and cultural amenities. 28,29 Yet, the political environment also matters for samesex couples, with greater concentrations of same-sex couples in less conservative places 30,31 and in regions with higher concentrations of other same-sex couples. 29 Within these regions, however, neighborhood selection can be influenced by several factors: Qualitative research finds strong evidence of the importance of other same-sex couples in neighborhood selection.…”
Section: Original Investigationmentioning
confidence: 99%
“…Partnered gay males and lesbians live virtually everywhere in the U.S.; they live in all the states and metropolitan areas and in most of the counties. However, most (around 85%) live in metropolitan statistical areas (Simmons and O'Connell, 2003, p. 2;Gates and Ost, 2004;Walther et al, 2011). Also, prior research (Black et al, 2000(Black et al, , 2002Gates and Ost, 2004;Walther and Poston, 2004;Walther et al, 2011;Gates, 2013;among others) shows considerable variation among the metropolitan areas with respect to the prevalence of gay male and lesbian partnering.…”
mentioning
confidence: 99%
“…However, most (around 85%) live in metropolitan statistical areas (Simmons and O'Connell, 2003, p. 2;Gates and Ost, 2004;Walther et al, 2011). Also, prior research (Black et al, 2000(Black et al, , 2002Gates and Ost, 2004;Walther and Poston, 2004;Walther et al, 2011;Gates, 2013;among others) shows considerable variation among the metropolitan areas with respect to the prevalence of gay male and lesbian partnering. These very different distributions of gay males and lesbians are of interest if only for the fact that they are sometimes associated with the political and social visibility of gay males and lesbians.…”
mentioning
confidence: 99%
See 1 more Smart Citation